2022
DOI: 10.53819/81018102t6037
|View full text |Cite
|
Sign up to set email alerts
|

Waste Management Practices Influence on Operating Cost among Selected Classified Hotels in Nakuru County, Kenya

Abstract: The world is currently battling the challenge of environmental degradation which is rising at an alarming rate. The situation is greatly attributed to poor waste management. The hospitality industry being a major consumer of resources contributes a lot towards waste generation. Regardless of the high level of waste generation, a lot of hotels continue to use improper waste management practices. The purpose of this study was to examine the effect of waste management practices on operating cost of classified hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Waste management is also an important consideration for the tourism industry, as it can have a significant economic impact. For example, the hospitality industry is one of the most resource-intensive industries and generates a lot of waste, which can lead to environmental degradation if not managed properly (Agesa et al, 2022). In addition, tourism infrastructure in protected areas can increase the demand for waste management (Claassens et al, 2022).…”
Section: Waste Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Waste management is also an important consideration for the tourism industry, as it can have a significant economic impact. For example, the hospitality industry is one of the most resource-intensive industries and generates a lot of waste, which can lead to environmental degradation if not managed properly (Agesa et al, 2022). In addition, tourism infrastructure in protected areas can increase the demand for waste management (Claassens et al, 2022).…”
Section: Waste Managementmentioning
confidence: 99%
“…However, poor waste management practices can lead to increased operational costs for hotels. A study conducted in Kenya found that waste management practices affect hotel operating costs, and waste reduction has a negative and statistically significant effect on operating costs (Agesa et al, 2022).…”
Section: Waste Managementmentioning
confidence: 99%
See 1 more Smart Citation